DEVELOPING A METHODOLOGY FOR TEACHING 3D MODELING IN SCHOOLS USING ARTIFICIAL INTELLIGENCE RESOURCES AND THE BLENDER PROGRAM - Zhamalova С.А.; Tagai А.М. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
The article explores the development of a teaching methodology that integrates artificial intelligence technologies and the capabilities of the Blender program to foster three-dimensional modeling skills within the secondary education system. The aim of the study is to organize 3D modeling lessons based on innovative approaches that promote students’ spatial thinking, creativity, and engineering abilities. The article analyzes the theoretical foundations of 3D modeling, its significance in education, and the potential for personalizing and adapting the learning process through the use of artificial intelligence tools. A pedagogical experiment was conducted as part of the research, and its results practically confirmed the effectiveness of the proposed methodology. The findings are aimed at improving digital educational content for school students and integrating modern technologies into the learning process.